Judicial Activism Of The Constitutional Court In Rulings On The Review Of Laws - Karolus Charlaes Bego; Patawari; Arliyanda; Ricky Marpaung; Adeh Dwi Putra M (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Judicial activism exercised by the Constitutional Court of Indonesia has become a prominent and contested phenomenon in the development of Indonesian constitutional law. This form of judicial behavior arises when the Court, in performing its authority to review statutes against the 1945 Constitution of the Republic of Indonesia, goes beyond annulling legal provisions and adopts progressive constitutional interpretations that effectively generate new normative frameworks. Such practices have sparked scholarly debate regarding the limits of judicial authority within the constitutional system based on the separation of powers. On one hand, judicial activism is regarded as a legitimate constitutional mechanism to safeguard human rights and citizens’ constitutional entitlements, particularly in situations where the legislature fails to adequately address demands for justice. On the other hand, excessive judicial intervention is criticized for potentially exceeding the Court’s role as a negative legislator and for creating imbalances in the relationship among state institutions. This study aims to examine the concept of judicial activism within Indonesia’s constitutional framework, analyze the constitutional basis of the Constitutional Court’s authority in judicial review, and explore how judicial activism is reflected in several landmark and progressive Constitutional Court decisions. The research employs a normative legal method using statutory, conceptual, and case-based approaches. The data are obtained through an extensive review of legislation, legal doctrines, and relevant national legal journals. The findings indicate that judicial activism practiced by the Constitutional Court plays a crucial role in strengthening constitutional supremacy and enhancing the protection of citizens’ constitutional rights. Nevertheless, such judicial activism must be exercised with due restraint and proportionality in order to prevent judicial overreach that could undermine the principle of checks and balances in a democratic state governed by the rule of law.